2017
DOI: 10.1130/g39660.1
|View full text |Cite
|
Sign up to set email alerts
|

Building up or out? Disparate sequence architectures along an active rift margin—Corinth rift, Greece

Abstract: Early Pleistocene synrift deltas developed along the southern Corinth rift margin were deposited in a single, dominantly lacustrine depocenter and were subject to the same climate-related base-level and sediment supply cyclicity. Two synrift deltas, just 50 km apart, show markedly different sequence geometry and evolution related to their location along the evolving border fault. In the west, strongly aggradational fan deltas (>600 m thick; 2–4 km radius) deposited in the immediate hanging wall of the active b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Solid lines show observable trajectories in the transition zone and dashed lines show our interpretation of retrogradation back to the fault and/or correlative surfaces to down‐dip maximum flooding surfaces. Kerinitis cross‐section from Gawthorpe, Andrews, et al () after Backert et al ()…”
Section: Stratal Stacking Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid lines show observable trajectories in the transition zone and dashed lines show our interpretation of retrogradation back to the fault and/or correlative surfaces to down‐dip maximum flooding surfaces. Kerinitis cross‐section from Gawthorpe, Andrews, et al () after Backert et al ()…”
Section: Stratal Stacking Patternsmentioning
confidence: 99%
“…Complementary field studies have shown that sequence boundary development is best expressed at fault tip regions (Dorsey & Umhoefer, —Loreto Basin) and the observed stratigraphic cyclicity has been attributed to fault‐related subsidence events (Dorsey et al, —Loreto Basin) and climatic forcing (Dart et al, ; Backert et al, —Gulf of Corinth). Marked differences occur in the sequence stratigraphy of two coeval fan deltas 50 km apart, due to contrasting tectonic controls between footwall (Kryoneri) and hangingwall (Kerinitis) sites (Gawthorpe, Andrews, et al, ). However, along‐strike and down‐dip variation on smaller length‐scales (<10 km) within the same hangingwall basin has not yet been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Barrett et al (2019) quantify the minimum period of deposition, average subsidence and sedimentation rates at the Kerinitis and Selinous fan deltas as >451 and 615 kyr, and 0.65 and >1.77 m/ kyr, respectively, based upon stratigraphic observations. Previous studies focus on the facies and stratigraphic architecture of the axial sections of the Kerinitis and Selinous fan deltas (Dart et al, 1994;Gawthorpe et al, 1994;Backert et al, 2010;Gawthorpe et al, 2017b;Barrett et al, 2019). Previous studies focus on the facies and stratigraphic architecture of the axial sections of the Kerinitis and Selinous fan deltas (Dart et al, 1994;Gawthorpe et al, 1994;Backert et al, 2010;Gawthorpe et al, 2017b;Barrett et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
“…Numerical modelling was used to quantify the amplitude of climate-induced lake-level changes in Lake Corinth during the Early-Middle Pleistocene at 10-15 m (Barrett et al, 2019). Previous studies focus on the facies and stratigraphic architecture of the axial sections of the Kerinitis and Selinous fan deltas (Dart et al, 1994;Gawthorpe et al, 1994;Backert et al, 2010;Gawthorpe et al, 2017b;Barrett et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation